Respiratory exchange ratio as an alternative to estimate ventilator threshold in long distance runners - Dellagrana, R. A.; Sakugawa, R. L.; Follmer, B.; Lemos, E. C.; Diefenthaeler, F.; de Campos, W. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Objective: The aim of the present study was to evaluate the use of respiratory exchange ratio (RER) as a criterion for estimating ventilatory threshold (VT) during graded treadmill test in long-distance runners. Methods: Nineteen male long-distance runners volunteered to participate in this study (17.9 ± 0.9 years, 173 ± 0.6 cm and 65.7 ± 7.9 kg). An incremental protocol was performed with initial speed of 10 km/h with increments of 1 km/h every 1 minute until voluntary exhaustion. The variables measured were oxygen uptake (VO2), VT, intensity corresponding to RER level of 1.0 (iRER1.0), peak velocity (PV), heart rate (HR), and rate of perceived exertion (RPE). One-way repeated measures analysis variance was used to compare the VO2, PV, HR, iRER1.0, and RPE with first ventilatory threshold (VT1), second ventilatory threshold (VT2), iRER1.0, and exercise intensity (speed) at which maximal oxygen uptake occurs (IVO2max). A post hoc test was performed using Bonferroni procedure. The Pearson correlation was used to verify the relationship between each parameter. The significance level was set at p<0.05. Results: There was no significant difference between iRER1.0 and VT2 parameters (Table 1). The correlations were significant between iRER1.0 and VT2 parameters for absolute and relative VO2, speed, and HR (r=0.95; r=0.60; r=0.72; r=0.81, respectively). Conclusion: Results suggest that iRER1.0 criterion can be used to estimate VT2 in long distance runners. This observation may have important practical implication for runners, due to its simplicity to identification during the gas analyses.